Determination of amino groups on functionalized graphene oxide for polyurethane nanomaterials: XPS quantitation vs. functional speciation. Issue 21 (21st February 2017) - Ederer, Jakub; Janoš, Pavel; Ecorchard, Petra; Tolasz, Jakub; Štengl, Václav; Beneš, Hynek; Perchacz, Magdalena; Pop-Georgievski, Ognen
Abstract : Simple spectrophotometric method for the estimation of accessible amino groups and preparation of polyurethane nanocomposites. Abstract : Amino-functionalized graphene oxide was reacted with isocyanate monomer to evaluate the potential application of GO-NH2 as a functional filler for the preparation of polyurethane nanocomposites. A set of advanced techniques (XRD, FTIR spectroscopy, Raman spectroscopy, and TEM) was used to characterize the functionalized samples, together with elemental analysis and XPS, which provided valuable information on the total N content and the nitrogen (chemical) speciation, respectively. In addition, a simple and fast spectrophotometric method was developed for the estimation of accessible amino groups (functional speciation). The method is based on the interaction of NH2 groups with the anionic dye acid orange 7 under appropriate conditions (pH = 3.6) and shows good precision. It can be advantageously used for the fast evaluation of the GO-NH2 reactivity with isocyanate monomer and its applicability as the polymer filler.